2018
DOI: 10.1177/0196859918771891
|View full text |Cite
|
Sign up to set email alerts
|

“What a Loser That Guy Was”: Norm Macdonald’s Humorous Critique of the Romantic/Warrior Narrative

Abstract: Illness narratives are stories that focus on, or are inspired by, the sometimes life-altering experience of illness. Most narrative constructions of these illness experiences are built upon one of three broad narrative “skeletons.” One skeletal subform, the romantic/warrior narrative, is critiqued by comedian Norm Macdonald in a humorous anecdote that mocks the expectation that cancer patients must wage an epic and heroic battle against their pernicious cancer to have a chance to survive. Macdonald explicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…While not applicable to all situations, this study found that humor may help illustrate patients’ medical decisions. Humor makes the story more honest (Iannarino, 2018b), and reveals the narrator’s authentic values and judgments behind their decision, even if it is not mainstream. For example, when a patient stated she would be glad to choose to remain nude if it reduced the pain of wound cleaning, the story brought a delightful release by challenging the belief about maintaining dignity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not applicable to all situations, this study found that humor may help illustrate patients’ medical decisions. Humor makes the story more honest (Iannarino, 2018b), and reveals the narrator’s authentic values and judgments behind their decision, even if it is not mainstream. For example, when a patient stated she would be glad to choose to remain nude if it reduced the pain of wound cleaning, the story brought a delightful release by challenging the belief about maintaining dignity.…”
Section: Discussionmentioning
confidence: 99%
“…They can also serve to empower, adding normalcy to the stories of marginalized patients (Pruulmann-Vengerfeldt & Buchholtz, 2018). Incorporating humor into illness stories can indicate that the narrators have become more reflective about their experiences and have carefully designed stories that better reveal their lives, a life that sometimes even hints at flaws in our culture (Iannarino, 2018b). When patients share narratives, humor’s intimacy makes it easier to discuss suffering, drawing the storyteller closer to their audience (Pruulmann-Vengerfeldt & Buchholtz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%